2015
DOI: 10.1007/s00248-015-0659-7
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity and Co-occurrence Patterns of N2-Fixing Communities in a CO2-Enriched Grassland Ecosystem

Abstract: Diazotrophs are the major organismal group responsible for atmospheric nitrogen (N2) fixation in natural ecosystems. The extensive diversity and structure of N2-fixing communities in grassland ecosystems and their responses to increasing atmospheric CO2 remain to be further explored. Through pyrosequencing of nifH gene amplicons and extraction of nifH genes from shotgun metagenomes, coupled with co-occurrence ecological network analysis approaches, we comprehensively analyzed the diazotrophic community in a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…The dominance of a few nifH OTUs was also previously observed in a grassland ecosystem, where the 15 most abundant OTUs accounted for 67.8% of the total captured nifH sequences in that ecosystem (Tu et al . ). Third, consistent with what has been observed for macrocommunities such as plant and animal communities, rainforests were found to have nifH OTU richness values twice that observed for temperate forest ecosystems.…”
Section: Discussionmentioning
confidence: 97%
“…The dominance of a few nifH OTUs was also previously observed in a grassland ecosystem, where the 15 most abundant OTUs accounted for 67.8% of the total captured nifH sequences in that ecosystem (Tu et al . ). Third, consistent with what has been observed for macrocommunities such as plant and animal communities, rainforests were found to have nifH OTU richness values twice that observed for temperate forest ecosystems.…”
Section: Discussionmentioning
confidence: 97%
“…New research using molecular techniques will reveal the true diversity of diazotrophic bacteria in agricultural and natural ecosystems and their potential to be used as inoculants in agricultural systems. Additionally, co-occurrence network analysis using nifH sequence data indicated the presence of complex co-occurrence patterns in the free-living diazotrophs than that known in symbiotic diazotrophs [202]. Such novel insights in to the ecology of diazotrophs may lead to development of inoculant mixtures that promote overall N 2 fixation.…”
Section: Discussionmentioning
confidence: 96%
“…The RMT-based approach is a widely used and robust tool for network construction and has been successfully used to construct various networks, including gene regulatory networks (Zhou et al, 2010; Lin et al, 2011, 2013), functional molecular ecological networks (Zhou et al, 2010) and phylogenetic molecular ecological networks (Zhou et al, 2011; Tu et al, 2016). To construct reliable co-occurrence ecological networks, the RMT-based network method was used (Deng et al, 2015), and only OTUs observed in at least 8 of the 12 samples were used for subsequent network analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Culture-independent molecular technology has developed rapidly in recent years and has been acknowledged as a feasible approach to study complex microbial communities. Emerging high-throughput sequencing technologies can provide a comprehensive understanding of the specific microbial species that live and thrive in various environments (Logares et al, 2014), and network-based approaches have been successfully used to evaluate the influence of environmental disturbances on the whole community (Raes and Bork, 2008; Zhou et al, 2010) and analyze microbial interactions in diverse habitats, including marine (Wang Y. et al, 2015), soil (Tu et al, 2015), acid mine drainage (Kuang et al, 2016) and groundwater environments (Deng et al, 2015). However, relevant research on microbial interactions during algal blooms is still limited, especially for the relationship between algae and associated bacteria.…”
Section: Introductionmentioning
confidence: 99%